Mixed-method evaluation of watershed management : practices from Kushk-Abad Basin, Iran - Mohammadi Golrang, Bahram (SpringerBriefs in environmental science,, 2017)
This volume evaluates technical and social aspects of a watershed management program in the Kush-Abad Watershed Basin in Iran. Author Bahram Mohammadi Golrang offers a way forward for a more integrated means to evaluate large scale rural environmental management projects, their effects on the physical environment, how to engage the public in such projects, and how nearby communities interact with them and perceive their effects. The analysis presented here focuses on land treatment efforts initiated by the Watershed Management Organization of Iran, and evaluation spans the project-planning stage through the project's implementation to citizens' perceptions of the project after it was completed. Project planners -- especially those in developing countries -- will find the lessons in this case study very useful in planning technically sound projects that achieve participation and satisfaction from local populations.